FIXED PROSTHETIC CONSTRUCTIONS WITH USING OF HIGH VOLUME DIGITAL SCANNING TECHNIQUES - Hasiuk, P.A.; Radchuk, V.B.; Hasiuk, N.V.; Rosolovska, S.O.; Demkovych, A.Ye.; Vorobec, A.B. (World of Medicine and Biology, 2017)
In order to determine the depth of preparing hard tissues in creating bevelled classic rounded ledge in the cervical area, the system CAD – volume digital scanner «Arcad Premium» on the unit «CAD / CAM ARCADIA» was modeled an artificial crown and received data about its thickness ledge area, which is 0.845 mm in this clinical case. The second group of observations included cases in which odontopreparation for full metal-ceramic crowns conducted with maximum preservation of cervical hard tissues of the tooth crown – forming the «symbol ledge». To determine the depth of preparation of dental hard tissues when creating a «symbol ledge» in the cervical area, as in the previous case was made unmodeling artificial crown, and obtain data of its thickness in the area of the ledge, which is 0.319 mm in this clinical case. To sum everything up, we can say that the experiment with using the Digital high volume scanning to determine the depth preparation of the experimented teeth by the young dentists, enables more accurate and carefully approach to the rationality of the depth of odontopreparation for non-removable prosthetic constructions.
Keywords: Prosthetics; CAD / CAM; the cervical ledge; artificial crown